Comparative effects of room-temperature water, cold water, normal saline, and aloe vera as first aid on burn wound healing in a rat model: An experimental study - Ruris Haristiani; Rondhianto; Rismawan Adi Yunanto; Baskoro Setioputro; Azkiatulfikroh; Laily Nailul Farih; Trisya Ainur Alula (Nursing and Health Sciences Journal (NHSJ), 2026)
Immediate first aid influences burn depth, infection risk, and healing. Common options include room-temperature water, cold water, normal saline, and Aloe vera, but direct comparative evidence remains limited. This study compared these interventions for burn wound healing in rats. A true experimental post-test-only control group design was used. Thirty male Wistar rats were randomly allocated to six groups (five per group). Standardized superficial partial-thickness burns were induced with a heated iron plate. Interventions comprised room-temperature water plus Burnazin, cold water plus Burnazin, normal saline plus Burnazin, room-temperature water plus Aloe vera, Aloe vera without irrigation, and room-temperature water plus vaseline. Wound diameter and macroscopic appearance were evaluated on days 1, 3, 7, and 14. Between-group differences were analyzed using one-way ANOVA (p < 0.05). Baseline wound diameter was 2.15 cm in all groups. Wound diameter increased on day 3, then decreased progressively on days 7 and 14. On day 14, the smallest mean diameters were observed in Aloe vera without irrigation (1.85 ± 0.29 cm), room-temperature water plus Burnazin (1.86 ± 0.31 cm), and room-temperature water plus vaseline (1.88 ± 0.26 cm). The largest diameter was observed in normal saline plus Burnazin (2.16 ± 0.42 cm). No statistically significant differences were found among groups on days 3, 7, or 14 (p = 0.056, 0.218, and 0.739). All interventions showed progressive wound healing. Aloe vera without irrigation showed a favorable but non-significant trend toward smaller wounds, requiring further verification.